Renal immature teratoma in a male adult: A case report and literature review. Issue 35 (August 2018) - Zhang, Xiao-long; Xu, Gang; Li, Jun-long; Pan, Shou-hua; Yan, Jia-Jun
Abstract: Rationale: Teratomas commonly arise in the gonads, including ovary and testis. The kidney is one of the most rare regions of primary teratoma. To date, about 19 cases of renal teratoma have been reported, and only 3 articles have reported renal immature teratoma; however, all of them occur in infant or children. In the present study, we reported a renal inmature teratoma in a male adult. Patient concerns: The present patient was a middle-aged man with aching pain in the left waist, and contrast-enhanced CT showed a lump in the left kidney with mild-to-moderate enhancement, and a low density small necrotic area was seen in the center. Diagnosis, interventions, and outcomes: The patient underwent radical nephrectomy. Based on postsurgical histopathology, the final diagnosis of this case was renal immature teratoma. Postoperative chemotherapy was carried out, and the patient has been followed-up for 18 months without tumor recurrence. Lessons: Adult renal immature teratoma is rare, and the diagnosis is mainly based on the pathological findings.